2001
DOI: 10.1159/000049163
|View full text |Cite
|
Sign up to set email alerts
|

Somatostatin, Its Receptors and Analogs, in Lung Cancer

Abstract: Despite developments in diagnosis and treatment, lung cancer is the commonest cause of cancer death in Europe and North America. Due to increasing cigarette consumption, the incidence of the disease and resultant mortality is rising dramatically in women. Novel approaches to the management of lung cancer are urgently required. Somatostatin is a tetradecapeptide first identified in the pituitary and subsequently throughout the body particularly in neuroendocrine cells of the pancreas and gastrointestinal tract … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0
4

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(41 citation statements)
references
References 132 publications
(250 reference statements)
1
36
0
4
Order By: Relevance
“…Somatostatin analogs have been proposed in the treatment of these tumors, either alone particularly as high-energy radioisotope-labeled peptide (octreotide) or as adjuvant therapy. Similar observations and conclusions have been made and proposed in cases of small cell lung cancer and bronchial carcinoid disease (O'Byrne et al 2001). In fact, all so-called neural crest or neuroendocrine tumors (insulinomas, glucagonomas, gastrinomas) have been shown to express somatostatin receptors and to respond, sometimes dramatically, to long-acting analogs of somatostatin.…”
Section: Somatostatinsupporting
confidence: 80%
“…Somatostatin analogs have been proposed in the treatment of these tumors, either alone particularly as high-energy radioisotope-labeled peptide (octreotide) or as adjuvant therapy. Similar observations and conclusions have been made and proposed in cases of small cell lung cancer and bronchial carcinoid disease (O'Byrne et al 2001). In fact, all so-called neural crest or neuroendocrine tumors (insulinomas, glucagonomas, gastrinomas) have been shown to express somatostatin receptors and to respond, sometimes dramatically, to long-acting analogs of somatostatin.…”
Section: Somatostatinsupporting
confidence: 80%
“…The National Comprehensive Cancer Network Guidelines (NCCN) recommends application of chemotherapy for small-cell lung cancer in extrapulmonary NEC patients because of histopathological similarities between small-cell lung cancer and NEC [16]. A randomized controlled trial that compared cisplatin-irinotecan combination therapy with cisplatin-etoposide combination therapy for extensive small-cell lung cancer was conducted in Japan [17] and demonstrated that cisplatin-irinotecan combination therapy is more suitable for extensive disease of small-cell lung cancer than cisplatin-etoposide combination therapy.…”
Section: Discussionmentioning
confidence: 99%
“…4 In recent years, several studies have suggested that SST functions as a tumor suppressor gene and possesses potent antitumor and antisecretory activity in several human cancers in vitro and in vivo. [5][6][7][8] Aberrant methylation of promoter CpG islands upstream of tumor suppressor genes is now well established as a major epigenetic mechanism of gene inactivation in tumorigenesis, 9 including ESCC and EAC. 10,11 More recently, data from our laboratory have shown that the SST promoter is methylated in 80% of human colon cancers, and that 5-aza-2 0 -deoxycytidine (5-Aza-dC) reverses SST promoter hypermethylation and restores SST mRNA expression in colon cancer cell lines.…”
Section: Conclusion Sst Promoter Hypermethylation Ismentioning
confidence: 99%